Association of methotrexate pathway gene polymorphisms with methotrexate efficacy and toxicity in Malaysian patients with rheumatoid arthritis - Sha, Hong Xi (2020)
Rheumatoid arthritis (RA) is delineated as chronic systemic inflammation affecting joints mediated by autoimmunity. Methotrexate (MTX) is the most widely used disease modifying anti-rheumatic drug (DMARD) for RA. Multiple studies attempted to understand the genetic factors of single nucleotide polymorphisms (SNPs) in affecting therapeutic outcomes and side effects. However, there is no finding regarding the association between SNPs and treatment outcomes of MTX monotherapy among RA patients in Malaysia. This study investigated the impact of nine single SNPs, which reside in MTX metabolic genes, on MTX efficacy and toxicity in RA patients. Six hundred and forty seven (647) RA patients (female : male = 574 : 73) were sampled from Sunway Medical Centre, Hospital Tuanku Ja'afar Seremban and Hospital Selayang. They were on MTX monotherapy (minimum 15 mg per week) for at least 3-month treatment and 6-month follow-up. A total of forty-three (43) RA patients were excluded from the MTX efficacy study because serious side effects to MTX were observed in less than 3 months. All 647 RA patients were included in the MTX toxicity study. Real-time TaqMan discrimination assay was performed to determine the alleles in five MTX metabolic genes using patient samples. Chi-square test and logistic regression were performed to examine the association between SNPs and MTX efficacy or MTX toxicity. Analysis of all 647 patients indicated that none of the SNPs studied were associated with either MTX efficacy or MTX toxicity according to the Chi-square test and binary logistic regression. However, stratification by self-identified ethnic group revealed that SNPs were significantly different between Malay (n = 153), Chinese (n = 326) and Indian (n = 168): particularly an association with MTX efficacy was observed in Malay patients, rs2372536 (ATIC 347C>G) (OR=0.5478, 95%CI=0.340-0.884, p = 0.013) and rs4673993 (ATIC 675T>C) (OR=0.5247, 95%CI=0.325-0.848, p = 0.008). Based on the inheritance models, the following conclusions have been made: 1) rs2372536 (ATIC 347C>G) was associatedwith adequate responders in Malay patients under the dominant and additive models; 2) the minor allele under three genetic models (dominant, recessive and additive) showed rs4673993 (ATIC 675T>C) association with adequate responders in Malay patients; 3) SNP rs1801131 (MTHFR 1298A>C) had an association with MTX efficacy in Indian patients (OR=2.172, 95%CI=1.125-4.197, p=0.021); 4) applying a dominant genetic model, rs1801131 (MTHFR 1298A>C) had showed an association with inadequate responders (IR) in Indian patients. Variation of MTHFR derived from rs1801131 (MTHFR 1298A>C) leads to reduced enzyme activity as it has been reported previously. The IR response of rs1801131 (MTHFR 1298A>C) is in congruent with previous reports but it seems unexplainable with the decreased activity of MTHFR. The rs2372536 (ATIC 347C>G) and rs467399 (ATIC 675T>C) are found in 5-aminoimidazole-4-carboxamide ribonucleotide (AICAR) transformylase/inosine monophosphate (IMP) cyclohydrolase (ATIC). The effect of these variants on ATIC activity may achieved through involving in gene regulation of ATIC and / or linkage disequilibrium with another coding SNPs. In conclusion, stratification by self-identified race confirmed that the rs2372536 (ATIC 347C>G), rs467399 (ATIC 675T>C) and rs1801131 (MTHFR 1298A>C) are associated with MTX efficacy in Malaysian RA patients but these SNPs exert different impacts in three Malaysian ethnic groups.